Two new species of Leptothorax ’Nesomyrmex’ fossils in Dominican amber (Hymenoptera: Formicidae). - Andrade, Maria L.; Urbani, Cesare Baroni; Brandão, Carlos Roberto Ferreira; Wagensberg, Jorge (Contributions to Entomology = Beiträge zur Entomologie, 1999)
Two new fossil species of Neotropical Leptothorax ’Nesomyrmex’ are described from Dominican amber (probably Miocene). Leptothorax caritatis, is described based on two workers from two samples. L. caritatis is close to the recent L. wilda Smith known from Brownsville, Texas, and from orchids of unknown Mexican provenance imported in the USA. A second Dominican amber species, L. dominicanus, is described based on a single worker specimen and is close to the recent L. echinatinodis Forel from Central and South America. It is noteworthy that both fossils exhibit the plesiomorphic leptothoracine (and formicid) condition of 12-jointed antennae, a trait distinguishing them from their closest recent relatives, which have 11-jointed antennae. Nomenclatural Acts caritatis Andrade et al., 1999 (Leptothorax), spec. n. dominicanus Andrade et al., 1999 (Leptothoraxs), spec. n.